USEEIO: A new and transparent United States environmentally-extended input-output model - Yang, Yi; Ingwersen, Wesley W.; Hawkins, Troy R.; Srocka, Michael; Meyer, David E. (Journal of cleaner production, 2017)
National-scope environmental life cycle models of goods and services may be used for many purposes, not limited to quantifying impacts of production and consumption of nations, assessing organization-wide impacts, identifying purchasing hotspots, analyzing environmental impacts of policies, and performing streamlined life cycle assessment. USEEIO is a new environmentally-extended input-output model of the United States fit for such purposes and other sustainable materials management applications. USEEIO melds data on economic transactions between 389 industry sectors with environmental data for these sectors covering land, water, energy and mineral usage and emissions of greenhouse gases, criteria air pollutants, nutrients and toxics, to build a life cycle model of 385 US goods and services. In comparison with existing US models, USEEIO is more current with most data representing year 2013, more extensive in its coverage of resources and emissions, more deliberate and detailed in its interpretation and combination of data sources, and includes formal data quality evaluation and description. USEEIO is assembled with a new Python module called the IO Model Builder capable of assembling and calculating results of user-defined input-output models and exporting the models into LCA software. The model and data quality evaluation capabilities are demonstrated with an analysis of the environmental performance of an average hospital in the US. All USEEIO files are publicly available bringing a new level of transparency for environmentally-extended input-output models. •We describe a new US Environmental Protection Agency national life cycle model of 385 US goods and services.•This environmentally-extended IO model targets current conditions and covers a comprehensive set of resources and emissions.•All model data are publicly available as well as the IO Model Builder program created to assemble it.•The model will be used to support sustainable materials management.